Analysis of Factors Influencing Nurses' Motivation Based on Self-Determination Theory on the Implementation of Health Education to Pre-Operation Patients - Tri Juningaju Ambarwati; Indah Lestari; Ima Rahmawati; Tri Ratnaningsih; Jajuk Retnowati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Low motivation can affect the quality of nurses' performance, especially in carrying out the duties and roles of nurses in hospitals. One of the hospital personnel who is vulnerable to decreased motivation is nurses. Therefore, support is needed to increase motivation in nurses so that they can improve nurse performance, especially in providing health education to patients in hospitals. Objective: To analyze factors that influence nurse motivation based on self-determinant theory towards the implementation of health education to pre-operative patients at Dr. Soetomo Hospital, Surabaya. Methods: This study used a correlation analytic design with a cross-sectional approach. The sample in the study was 115 nurses taken using a simple random sampling technique. The instruments used were intrinsic and extrinsic motivation questionnaires, as well as a questionnaire on the implementation of health education. Data were analyzed using a logistic regression test. Results: There is a significant relationship between extrinsic factors including: rewards, awards, punishments, internal rules, external rules towards nurse motivation in providing health education to pre-operative patients with a significant p-value of the extrinsic motivation variable of 0.003. Conclusions: Nurses' motivation in providing health education to pre-operative patients is influenced by various intrinsic and extrinsic factors, therefore hospitals should provide interventions that can increase nurses' motivation so that health education to patients can be carried out properly.